1999
DOI: 10.1128/jcm.37.11.3725-3730.1999
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Survey of Recent β-Lactam-Resistant Pneumococcal Nasopharyngeal Isolates from Asymptomatic Children in Chile

Abstract: To assess pneumococcal strain variability among young asymptomatic carriers in Chile, we used serotyping, antibiotic susceptibility testing, and genotyping to analyze 68 multidrug-resistant pneumococcal isolates recovered from 54 asymptomatic children 6 to 48 months of age. The isolates represented capsular serotypes 19F (43 isolates), 14 (14 isolates), 23F (7 isolates), 6B (3 isolates), and 6A (1 isolate). Genotypic analysis, which included pulsed-field gel electrophoresis (PFGE) of chromosomal digests, penic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Similar conclusions were reached by Sogstad et al [19], based on PBP analysis with an indication of the PBP2x determinant. Consistent with other studies [10,23], we have found reduced profile variation in the PBP genes among the majority of β-lactam-sensitive isolates.…”
Section: Discussionsupporting
confidence: 92%
“…Similar conclusions were reached by Sogstad et al [19], based on PBP analysis with an indication of the PBP2x determinant. Consistent with other studies [10,23], we have found reduced profile variation in the PBP genes among the majority of β-lactam-sensitive isolates.…”
Section: Discussionsupporting
confidence: 92%
“…The strains selected for this study, namely R6, 5204, G54, Hungary19A‐6, and SP195 have MIC values of penicillinG as <0.016 μg/mL (14,20), 6 μg/mL (14,20), 2–4 μg/mL (45), <1 μg/mL (46) and <1 μg/mL (46) respectively. According to penicillin, MIC range that ≤0.06 as susceptible, 0.12–1 as intermediate resistant, and >1 as highly resistant (20).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, novel drug-resistant clones have been reported in France, former Czechoslovakia, Spain, Hungary, Japan, South Africa, the United States, Chile, England, etc. which tend to spread in a nationwide manner (6,13,16,17,19,35,37,45). The risk for colonization with and spread of antibiotic-resistant strains is related to younger-age children, occurrence of refractory middle ear infections, previous antibiotic consumption, and day care attendance (9,28,32).…”
mentioning
confidence: 99%